Strange worlds the vision of Angela Carter - Mulvey Roberts, Marie 1955-; Robinson, Fiona 1965- (Sansom & Company, 2016)
"Strange worlds. The vision of Angela Carter" celebrates the life and work of the hugely influential writer Angela Carter (1940-1992), 25 years after her death, and accompanies a major exhibition of the same name at the RWA (Royal West of England Academy), Bristol. Bringing together art and literature, Strange Worlds explores Carter's recurring themes of feminism, mysticism, sexuality and fantasy, through historically significant art works by Marc Chagall, William Holman Hunt, Dame Laura Knight, Leonora Carrington and John Bellany. These historical works sit alongside work by major contemporary artists including Ana Maria Pacheco, Eileen Cooper, Paula Rego and Alice Maher revealing the extent to which Angela Carter?s ideas have indirectly but profoundly influenced twenty-first century culture. The book contains reminiscences of those who knew and worked with Carter including close friends Christopher Frayling, Marina Warner, Christine Molan and her publisher, Carmen Callil (founder of Virago) each of whom offers a personal insight into Carter's unique and strange vision of the world. Exhibition: Royal West of England Academy, Bristol, UK (10.12.2016-19.03.2017)
Published to coincide with the exhibition "Strange worlds: the vision of Angela Carter", 10 December 2016-19 March 2017, Royal West of England Academy, Bristol
Keywords: Carter, Angela -- 1940-1992; Künstlerisches Werk; Ausstellungskatalog -- Royal West of England Academy -- 10.12.2016-19.03.2017 -- Bristol; Bildband